PENGARUH PELATIHAN KERJA, FASILITAS KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWANPT PROSEGUR CASH INDONESIA - Muhammad Reggy Fadilla (2021)
This research is a quantitative research that has the aim of testing, knowing, processing and proving the influence of Job Training, Work Motivation, and Work Facilities on the performance of PT Prosegur Cash Indonesia employees, with a total sample of 45 employees or respondents. The analysis technique used in this research is descriptive analysis and inferential analysis which consists of validity test, reliability test, coefficient of determination test, and hypothesis testing using SmartPLS 3.0 tool. The results of this study showed that (1) Job Training had a significant positive effect on employee performance at PT Prosegur Cash Indonesia, (2) work facilities had a significant positive effect on employee performance at PT Prosegur Cash Indonesia, (3) work motivation had a significant positive effect on employee performance at PT Prosegur Cash Indonesia, (4) Job Training, Work Facilities, and Work Motivation have a significant positive effect together on the performance of PT Prosegur Cash Indonesia employees.